1996
DOI: 10.1016/s0092-8674(00)81029-6
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking H2-M Complexes, Enigmatic Elements of the MHC Class II Peptide-Loading Pathway

Abstract: We have generated mice lacking H2-M complexes, critical facilitators of peptide loading onto major histo-compatibility complex class II molecules. Ab molecules in these mice matured into stable complexes and were efficiently expressed at the cell surface. Most carried a single peptide derived from the class II-associated invariant chain; the diverse array of peptides normally displayed by class II molecules was absent. Cells from mutant mice presented both whole proteins and short peptides very poorly. Surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
296
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(314 citation statements)
references
References 46 publications
16
296
0
2
Order By: Relevance
“…Indeed, other data suggested that positive selection is not greatly impacted by the specificity of the self peptides presented. Here, the experimental approaches were designed to limit the available peptide/ MHC repertoire to one face and to examine the impact on repertoire size (15)(16)(17)(18). It was shown that in such "single" peptide/MHC mice, a large and diverse repertoire was selected.…”
Section: Positive Selection Is Limited By Available Peptide-dependentmentioning
confidence: 99%
“…Indeed, other data suggested that positive selection is not greatly impacted by the specificity of the self peptides presented. Here, the experimental approaches were designed to limit the available peptide/ MHC repertoire to one face and to examine the impact on repertoire size (15)(16)(17)(18). It was shown that in such "single" peptide/MHC mice, a large and diverse repertoire was selected.…”
Section: Positive Selection Is Limited By Available Peptide-dependentmentioning
confidence: 99%
“…Although crystallographic studies have not found any evidence for this possibility (58,60), studies with conformation-dependent Abs have suggested that peptide binding can affect the conformation of MHC class I (61, 62) and class II (43,44,59,(63)(64)(65) molecules and that such subtly altered conformations can affect recognition by TCRs (57,(65)(66)(67). Our observation that none of the hybrids reactive with A b EpIi Ϫ cells recognized H2-DM-deficient cells, and vice versa (Table I), is consistent with this idea.…”
Section: Peptide-dependence Of Alloreactive T Cell Responsesmentioning
confidence: 99%
“…It also seems likely that DM actions demonstrated via these complementation assays could be influenced by many additional experimental parameters, such as abnormal expression levels and functional contributions by recipient cell lines, making it difficult to assess the significance of these observations. Current thinking about the class II pathway has been strongly influenced by studies of DM mutant mice (22)(23)(24). The loss of DM function disrupts conventional Ag presentation and causes complex defects with respect to selection of mature CD4 ϩ T cells.…”
mentioning
confidence: 99%
“…The striking accumulation of A b /CLIP complexes alongside severely reduced peptide-loading capabilities strongly argues DM activity is required to mediate CLIP release and promote occupancy by diverse peptides under physiological conditions in normal APCs. As judged by the gain of reactivity toward wild-type class II molecules, mature CD4 ϩ T cells exclusively selected on A b /CLIP complexes exhibit somewhat incomplete tolerance toward natural self-peptides (22)(23)(24). Considerable evidence suggests these animals express a semidiverse TCR repertoire (25-28).…”
mentioning
confidence: 99%